THE BRIGADEIRO EDUARDO GOMES: AN ANALYSIS OF HIS BIOGRAPHICAL WORKS - Stringuetti, Lucas Mateus [UNESP] (Univ Brasilia, 2016)
The purpose of this text is to conduct a comparative analysis of biographical works written over time about Brigadeiro Eduardo Gomes. Thus, the following works will be analysed: Brigadeiro Eduardo Gomes (1945), by Gastao Pereira da Silva, O Brigadeiro da Libertacjo (1946), second edition, by Paulo Pinheiro Chagas and O Brigadeiro: Eduardo Gomes, trajetoria de um heroi (2011), written by Cosme Degenar Drumond. Hence, the goal is to discuss how Brigadeiro Eduardo Gomes's political profile was portrayed by the authors in their works when Brigadeiro ran for presidency representing the National Democratic Union (UDN) in 1945. Along with this goal, this article also aims to ascertain, in addition to the similarities and differences, how these works present their approach from the documental and historical point of view.
Keywords: Brigadeiro Eduardo Gomes; UDN; Biographical works